1994
DOI: 10.1007/bf00171411
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of a state-of-the-art neuro-SPET scanner and a dedicated neuro-PET scanner

Abstract: The physical performances of two current state-of-the-art scanners dedicated to functional imaging of the brain, one a single-photon emission tomography (SPET) scanner and the other a positron emission tomography (PET) scanner, have been compared under identical conditions. The aim of the study was to compare the capabilities of the devices under conditions resembling the routine clinical environment, as well as to consider other issues such as radiation burden for some common investigations. Both systems have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…2 '• 22 Therefore, the main factor for sensitivity is considered to be spatial resolution, if the two relatively wide-spread procedures F-18-DG-PET and rCBF-SPECT are compared and recent reports claimed that modern SPECT systems dedicated for brain SPECT have largely filled the described gap of sensitivity between PET and SPECT. 12 In this study sensitivity of interictal rCBF-SPECT increased from 69% for low spatial resolution SPECT systems to 84% for moderate-to high-resolution SPECT systems. The advanced MRI system also showed increased sensitivity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2 '• 22 Therefore, the main factor for sensitivity is considered to be spatial resolution, if the two relatively wide-spread procedures F-18-DG-PET and rCBF-SPECT are compared and recent reports claimed that modern SPECT systems dedicated for brain SPECT have largely filled the described gap of sensitivity between PET and SPECT. 12 In this study sensitivity of interictal rCBF-SPECT increased from 69% for low spatial resolution SPECT systems to 84% for moderate-to high-resolution SPECT systems. The advanced MRI system also showed increased sensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…12 Furthermore, reports focussing on interictal evaluation of epilepsy showed comparable sensitivity between PET and SPECT in this indication' 3" 4 and ictal rCBF-SPECT has proven to show superior sensitivity in the evaluation of epilepsy, regardless which imaging procedure has been used tor correlation.…”
Section: During Presurgical Evaluation Of Patients With Medi-mentioning
confidence: 99%
“…Animal PET scanners have a spatial resolution range of about 2 mm [10,11], while dedicated PET have a spatial resolution range of about 4Y6 mm [12,13] and DHC have a resolution of about 5 to 8 mm [14Y16]. Dedicated PET cameras and animal PET cameras also have a better detection limit because their sensitivity (in air with a line source) is 150 times greater in 3-D and 25 times greater in 2-D than DHC [15]. If the sensitivity and the maximum true coincidence counting rate are relatively lower in DHC compared to dedicated PET scanner [16], DHC with large NaI crystals allows the acquisition of whole rat body images when animal PET cameras need several bed positions [17].…”
Section: Discussionmentioning
confidence: 98%
“…Antagonists, such as flumazenil, have no effect on GABAergic transmission, but antagonise the effects of agonists and inverse agonists by competing for the receptor site. Apart from the benzodiazepines, other drugs such as barbiturates, ethanol, steroids, antihelminthics and some anaesthetic compounds also produce at least part of their Table 1 Comparison of some aspects of PET and SPECT &dquo;Comparison of spatial resolution of state-of-the-art brain dedicated SPECT and PET scanners, showed that, on average, the PET scanner had 10-15% better resolution (Bailey et al, 1994). pharmacological effects by allosterically modulating GABAAinduced chloride ion flux (Sieghart, 1992).…”
Section: Benzodiazepine Receptorsmentioning
confidence: 99%
“…SPECT is cheaper and is becoming more available in both clinical and research settings. The main SPECT developments in the last decade or so have been directed towards improving the counting capabilities and spatial resolution of systems (Bailey et al, 1994), the ultimate aim being quantitative imaging using appropriate radioligands (Blokland, Reiber and Pauwels, 1992;Blokland, 1994).…”
Section: Computerised Tomographic Imaging Of Benzodiazepine Receptorsmentioning
confidence: 99%